Trichoderma dumbbelliforme sp. nov. an undescribed fungus of order Hypocreales from India - T, Prameeladevi; Kamil, Deeba; Toppo, R. Sudeep; Choudhary, Shiv Pratap (Phytotaxa, 2021)
Trichoderma is an important genus of family Hypocreaceae, which contain nearly 375 known species. In current study, a new species Trichoderma dumbbelliforme collected from virgin forest soil of Nagaland and confirmed based on morphological and phylogenetic analyses. Morphologically, T. dumbbelliforme sp. nov. distinguished from other species of Trichoderma by producing nodules on sterile part of the conidiophores and pyriform to dumbbell shaped conidia with the size of 4.0–6.0×2.5–3.0µm and having two big guttulae at each end. Furthermore, the fungus was confirmed by molecular characterization using Translation elongation factor 1-α (tef-1) gene sequencing.  The phylogenetic relationship was established for generated sequence and many related ex-type sequences downloaded from NCBI GenBank by maximum-parsimony analysis. Tef-1 sequence data clarified the phylogenetic affinity to clade-1 of Trichoderma as per new authoritative guide line on molecular identification of Trichoderma. Phylogenetically, this new species of Trichoderma closely related to T. crassum, T. spirale, T. sulawesense, T. longisporum, T. virens, T. gelatinosum and T. gliocladium species. Therefore, the morphological comparisons were done with closely related species viz., T. crassum and T. spirale which lead to the conclusion that the collected taxon is new to science.